Satellite tracking of the World's largest bony fish, the ocean sunfish (Mola mola L.) in the North East Atlantic - Sims, D.W.; Queiroz, N.; Doyle, T.K.; Houghton, Jonathan; Hays, G.C. (Journal of Experimental Marine Biology and Ecology, 2009)
Satellite-linked archival transmitters were used to record the movements of three ocean sunfish (Mola mola) in the North East Atlantic. Patterns of depth use and temperature experienced by individual fish were integrated into 4-hour intervals throughout the tracking period and relayed via the Argos system. Data were recorded for 42, 90 and 54 days respectively from the three fish. The first two were tagged off southern Portugal at the end of February 2007 and travelled principally northward, while the third fish was tagged off west Ireland in August 2007 and travelled southward. These patterns are consistent with seasonal migration of ocean sunfish to high latitudes and their Subsequent return south. Maximum depths recorded by the three fish were 432 m, 472 m and 320 m respectively. All three individuals showed a diel pattern in depth use, occurring deeper during the day and shallower at night, a pattern consistent with sunfish tracking normally vertically migrating prey. Sunfish sometimes remained continuously at deeper (>200 m) depths during the day, but at other times they showed extensive movement through the water column typically travelling between their maximum depth and the surface within each 4-h period. The overall pattern to emerge was that ocean sunfish travel extensively in both horizontal and vertical dimensions, presumably in search of their patchily-distributed jellyfish prey.